Editorial: Keeping an eye on Ebola Virus Disease in South Sudan - Edward Eremugo Kenyi (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2018)
Between June and November 1976, the medical world was baffled by an outbreak of a ferocious haemorrhagic disease in Nzara, South Sudan (then part of Sudan). The disease subsequently spread to Maridi and Tombura towns. The World Health Organization (WHO) responded to the call by the Sudan government for support by sending a team of epidemiologists and doctors to investigate.